A Study of Relationship of Family Environment with Mental Health of Secondary School Students of Greater Noida Region India: Exploring the Impact of Family Environment on Mental Health of Secondary School Students in Greater Noida Region (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Adolescence is taken into account as a transition from childhood to adulthood. It is very important aspect in human life because many developmental changes take place in this period such as physical growth, peer emotions, mental development etc. The current study was undertaken to look at the connection between family environments with mental state of adolescents of Greater Noida Region. The family environment of the adolescents was assessed by using family environment scale by Dr. Harpreet Bhatia and Dr. N.K.Chadha (1993) and mental health of the adolescents was assessed by Mental Health Check list by Dr. Parmod Kumar (1992). 168 Adolescents including boys and girls were chosen from one school in urban area and one school from rural area equally through random sampling technique.The data was analyzed and interpreted by using statistical technique, mean, standard deviation, correlation and t-ratio. The current study can recommend appropriate measures to strengthen the connection of family atmosphere with mental state of adolescents.